Curcumin-Loaded Solid Lipid Nanoparticles from Curcuma longa Attenuate Inflammatory Cytokine Cascades in a Rat Model of Acute Peritonitis - Oliva Azalia Putri; Dedi Sucipto (HM Publisher, 2025)
Acute peritonitis remains a life-threatening intra-abdominal inflammatory condition with significant morbidity and mortality, particularly in resource-limited settings across Southeast Asia. Curcumin, the principal polyphenol of Curcuma longa L. (Zingiberaceae), has potent anti-inflammatory and antioxidant properties, but its clinical use is limited by poor oral bioavailability, rapid hepatic metabolism, and low aqueous solubility. This study evaluated the anti-inflammatory and antioxidant efficacy of curcumin-loaded solid lipid nanoparticles (Cur-SLNs) in a cecal ligation and puncture (CLP)-induced acute peritonitis rat model. Thirty male Wistar rats were randomized into five groups (n=6): sham, CLP+vehicle, CLP+free curcumin (100 mg/kg), CLP+Cur-SLN low dose (50 mg/kg), and CLP+Cur-SLN high dose (100 mg/kg). Cur-SLNs prepared by hot homogenization-ultrasonication had a mean particle size of 152.4±8.7 nm, polydispersity index 0.218±0.03, zeta potential −28.6±2.1 mV, and entrapment efficiency 87.3±3.2%. At 24 hours, Cur-SLN high dose significantly reduced TNF-α (89.6±18.3 versus 287.5±45.2 pg/mL, p<0.001), IL-6 (102.4±22.7 versus 312.4±52.8 pg/mL, p<0.001), and IL-1β (78.5±16.8 versus 245.6±41.3 pg/mL, p<0.001) compared with CLP-vehicle, with large effect sizes (Cohen's d 4.50–5.72), alongside attenuated oxidative stress, reduced bacterial burden, and preserved peritoneal histology. Cur-SLNs from Curcuma longa represent a promising herbal nanomedicine strategy for attenuating inflammatory cascades in acute peritonitis.